2011
DOI: 10.1186/1477-7819-9-1
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructive challenge of dermatofibrosarcoma protuberans in the female breast

Abstract: Dermatofibrosarcoma protuberans is an uncommon locally aggressive malignant neoplasm that most frequently appears in the trunk, followed by the extremities, head, and neck. But occurrence in the breast is extremely rare. We present a case of a 28-year-old woman, who had a history of trauma 5 years previously and excision 1 year before presentation at our clinic. We performed wide excision, together with microscopic and immunohistochemical analysis. No postoperative oncologic treatment was used and she remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…However, not much has been emphasized about aesthetic outcomes following tumor excisions. For example, Park et al, emphasized the reconstructive challenge of the breast DFSP following a wide excision [19]. In a case presented by Cavusoglu et al, reconstruction was achieved by an altered keyhole pattern, a technique commonly used in aesthetic breast reductions.…”
Section: Discussionmentioning
confidence: 99%
“…However, not much has been emphasized about aesthetic outcomes following tumor excisions. For example, Park et al, emphasized the reconstructive challenge of the breast DFSP following a wide excision [19]. In a case presented by Cavusoglu et al, reconstruction was achieved by an altered keyhole pattern, a technique commonly used in aesthetic breast reductions.…”
Section: Discussionmentioning
confidence: 99%
“…[2] It is caused by mutations of MENIN gene located on Chromosome 11q13.3. [3] Germline mutations in this gene lead to development of one or more components of the classic triad of parathyroid hyperplasia (90%), pancreatic neuroendocrine tumors (PET) (60%), and pituitary adenomas (40%). [4] Other recognized manifestations of MEN1 include carcinoid tumors of the bronchus, thymus and gastrointestinal tract; and cutaneous tumors such as lipomas, angiofibromas, collagenomas, and adrenocortical tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Incidence of adrenal involvement in MEN1 has been reported to be between 9 and 45% and incidence of adrenocortical carcinoma in MEN1 is around 2.6-6%. [3] Most of the cases of MEN1 presents with symptoms related either to hyperparathyroidism or pancreatic neuroendocrine tumors. Here, we report a case of MEN-1 in a 43-year-old female presented with features of rapidly progressive virilization and during workup was detected to have parathyroid adenoma, pancreatic tumors and adrenocortical carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature revealed a variety of surgical approaches to address DFSP of the breast. One patient underwent a mastectomy, one patient underwent a wide local excision with concomitant breast reduction, three patients underwent a wide local excision with fl ap reconstruction, one patient underwent a wide local excision with skin graft, and nine patients underwent wide local excision with primary closure ( Table 1 , [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Th e reconstructive challenge in DFSP of the breast is to balance the oncologic principles of adequate resection with the cosmetic goals of acceptable symmetry and contour.…”
Section: Case Descriptionmentioning
confidence: 99%
“…Th e most common location of DFSP is the trunk, with 25% of cases aff ecting the chest and shoulder areas (1). At least 40 case reports of DFSP in the breast have been reported, but less than half address the surgical management (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), which we describe here.…”
mentioning
confidence: 99%